Antibacterial Actinomycetes from Tropical Ecosystem Karst in South Sulawesi: Isolation, Characterization, and Bioactive Metabolite Profiling - Alimuddin Ali; Pasmawati Pasmawati; Rukman Muslimin; Alnadia Yusriya Hibatullah; Deni Frans Sakka; Christina Aryanti Pada Soa; Kusdianawati Buhaerah; Muharram Passitta (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The emergence of antimicrobial-resistant pathogens reinforces the critical need for new antibiotics sourced from unexplored microbial habitats. Actinomycetes remain the most prolific bacterial producers of bioactive secondary metabolites, yet tropical karst ecosystems and plant-associated rhizospheres in Indonesia remain poorly investigated despite their ecological complexity. This study aimed to isolate, screen, and characterize Actinomycetes from the karst and rhizospheric environments of South Sulawesi, Indonesia, and to identify isolates capable of producing antibacterial compounds. A total of 42 isolates were obtained using heat-shock pretreatment and selective Starch Casein Agar. Preliminary antagonistic assays against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218 identified four active isolates. Two isolates KMR 1E2 and SDR 2a exhibited strong inhibition (>30 mm) against S. aureus, while SDR 9.9 inhibited E. coli. Morphological and phenotypic characterization revealed diverse spore-chain architectures, colony color profiles, carbon and nitrogen utilization patterns, salinity tolerance, melanin production, and variable growth under different pH and temperature conditions. Ethyl acetate extracts of KMR 1E2 and SDR 2a demonstrated potent antibacterial activity, and TLC-bioautography identified three active metabolites (Rf 0.73, 0.48, 0.34), with the Rf 0.34 spot associated with an alkaloid-type compound. The minimum inhibitory concentration (MIC) of KMR 1E2 extract against S. aureus was 0.3125 mg/mL. This study confirms that tropical karst ecosystems in Indonesia are promising reservoirs of antibiotic-producing Actinomycetes and provides a foundation for future genomic and chemical elucidation studies